Secondary Tumors of the Ampulla of Vater: A Tale of Two Cases - Ali, Jafer; Khan, Asad; Ahmed, Mohamed H.; Madhotra, Ravi (Journal of Laboratory Physicians, 2021)
We report two cases of women with metastatic cancers to ampulla of Vater. The first was 91 years old and presented with severe anemia, due to upper gastrointestinal bleeding. She had history of renal cell cancer treated with nephrectomy 8 years ago and diagnosis confirmed to be metastasis of renal cell cancer to ampulla of Vater. The second patient was 54 years old with breast cancer, metastasis and developed obstructive jaundice; diagnosis confirmed to be breast metastasis in the ampulla of Vater. Secondary tumors of the ampulla of Vater due to breast cancer and renal cell cancer are rare findings and prognosis can be poor.
Keywords: ampulla of Vater; breast cancer; renal cell cancer